Climate change and Caribbean economies : implications, adaptation and risk management - Iyahen, Ekhosuehi (Caribbean Catastrope Risk Insurance Facility [S.l.], 2009)
Suggests that investing in adaptation initiatives that reduce the impact of climate change is essential for the future viability and sustainability of the economies of the Caribbean.